CALCULUS TEACHER’S COMPETENCIES AS CORRELATES OF STUDENTS’ LEARNING EXPERIENCES - Casinillo, Leomarich F (Sanata Dharma University Yogyakarta, 2023)
The good qualities of a calculus teacher are an asset in producing great results for students and themselves. This study aimed to investigate the different competencies of a calculus teacher as correlates of students' experiences in learning at Visayas State University, Philippines. The study employed selected secondary data from the existing study in literature such as competencies in teaching calculus subjects and different types of learning experiences of students. The study used some descriptive statistical measures to summarize the selected data and employed Spearman rho correlation to predict significant factors (teacher's competencies) that might influence the student's learning experiences. Results showed that teachers' competencies such as